ANALISIS KESESUAIAN KOMPETENSI LULUSAN SMK NEGERI 2 MAKASSAR DENGAN KEBUTUHAN DUNIA INDUSTRI - Ninik Septyani; Syahru; Abdul Muis Mappalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This study is a qualitative research with phenomenology approach, which aims at discovering the description of competency analysis of graduates of SMKN 2 Makassar based on the industrial business. The subjects of the study were the principal, teachers, students of SMKN 2 Makassar, and several employees in each industry who involved directly in the activities. Data were collected by employing purposive sampling that interviewed the principal, two skill teachers, four students majoring in Computer and Network Engineering, and eight employees. Data were obtained through semi-structured interview and documentation which related to the learning process for the development of students’ skills. Data were analyzed by employing data reduction, data display, and conclusion drawing. The results of the data were obtained from all the informants’ answers and appropriate document results which have met the skills specification for career requirement in the industry based on the skills acquired in the learning process at school inline with the implementation of 70% practical learning and 30% theory learning. The factors that affect the work readiness ofgraduates at SMKN 2 Makassar are interest, motivation, social environment, family support, and lack of socialization skills in a new environment and frequent differences of opinion among team members. Vocational high school graduates are also often faced with new technological devices that in general have not been mastered so they need cooperation and need time to learn more about thesetechnologies. Another factor that becomes an obstacle for graduates at SMKN 2 Makassar even though they have adequate skills, but each industry also prioritizes synchronization between skills and certificate level from each employee, especially in terms of promotion. This has resulted in several graduates of SMKN 2 Makassar who have been in the industry for years but do not get theopportunity to increase their career paths in accordance with their service period.